2013
DOI: 10.1088/2041-8205/775/1/l12
|View full text |Cite
|
Sign up to set email alerts
|

G 10.472+0.027: An Extreme Water Maser Outflow Associated With a Massive Protostellar Cluster

Abstract: An Australia Telescope Compact Array search for 22 GHz water masers towards 6.7 GHz class II methanol masers detected in the Methanol Multibeam (MMB) survey has resulted in the detection of extremely high velocity emission from one of the sources. The water maser emission associated with this young stellar object covers a velocity span of nearly 300 km s −1 . The highest velocity water maser emission is red-shifted from the systemic velocity by 250 km s −1 , which is a new record for high-mass star formation r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The MMB sources are also being followed up for the four ground-state, main-line OH maser transitions in the MAGMO survey , and for 22-GHz water maser emission (Titmarsh et al 2013(Titmarsh et al , 2014. de Villiers et al (2014) used the James Clerk Maxwell Telescope (JCMT) to observe a subset of the MMB masers, uncovering the characteristics of their associated CO outflow emission, explored in greater detail in de Villiers et al (2015).…”
Section: Mmb Investigations and Follow-up Programmesmentioning
confidence: 99%
“…The MMB sources are also being followed up for the four ground-state, main-line OH maser transitions in the MAGMO survey , and for 22-GHz water maser emission (Titmarsh et al 2013(Titmarsh et al , 2014. de Villiers et al (2014) used the James Clerk Maxwell Telescope (JCMT) to observe a subset of the MMB masers, uncovering the characteristics of their associated CO outflow emission, explored in greater detail in de Villiers et al (2015).…”
Section: Mmb Investigations and Follow-up Programmesmentioning
confidence: 99%
“…Within high-mass star formation regions, 10.472+0.027 is the most extreme, with features redshifted up to 250 km s −1 from the systemic velocity of the region and a total velocity range of nearly 300 km s −1 (Titmarsh et al 2013). Figure 3.…”
Section: Velocitiesmentioning
confidence: 99%
“…With no velocity shift between the RHCP and LHCP components, a magnetic field non-detection is reported in this work. This source is coincident with a complex high-mass star forming region (Pascucci et al 2004), identified as a 25,000-35,000 M high-mass proto-cluster G010.4722+0.0277 (Ginsburg et al 2012;Urquhart et al 2013) which hosts at least one very young late O, or early B star that may be actively accreting Titmarsh et al (2013).…”
Section: 376+0040mentioning
confidence: 84%
“…The GLIMPSE image shows two separate mid infrared sources with coincident maser emission, one with just the 1720-MHz OH maser and the other with the OH main lines at 1665-and 1667-MHz (MAGMO, Caswell 1998), 6.7-GHz methanol (Green et al 2010) and a water maser (that holds the record for highest velocity emission of any water maser associated with star formation Titmarsh et al 2013).…”
Section: 376+0040mentioning
confidence: 99%